2010
DOI: 10.1111/j.1365-246x.2010.04745.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying focal mechanism heterogeneity for fault zones in central and southern California

Abstract: S U M M A R YWe present a statistical analysis of focal mechanism orientations for nine California fault zones with the goal of quantifying variations of fault zone heterogeneity at seismogenic depths. The focal mechanism data are generated from first motion polarities for earthquakes in the time period 1983-2004, magnitude range 0-5, and depth range 0-15 km. Only mechanisms with good quality solutions are used. We define fault zones using 20 km wide rectangles and use summations of normalized potency tensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 50 publications
5
44
0
Order By: Relevance
“…The latter is calculated assuming a faster side velocity of 5.5 km s -1 and a velocity contrast of 10 per cent based on the tomographic results of Allam & Ben-Zion (2012). We do not require polarity reversal between FZHW and direct P waves because of the mixed complex focal mechanisms for events in the region (Bailey et al 2010). Arrivals from flagged events recorded at different stations are visually compared to remove erroneous picks such as emergent early phases similar to the noise.…”
Section: Resultsmentioning
confidence: 99%
“…The latter is calculated assuming a faster side velocity of 5.5 km s -1 and a velocity contrast of 10 per cent based on the tomographic results of Allam & Ben-Zion (2012). We do not require polarity reversal between FZHW and direct P waves because of the mixed complex focal mechanisms for events in the region (Bailey et al 2010). Arrivals from flagged events recorded at different stations are visually compared to remove erroneous picks such as emergent early phases similar to the noise.…”
Section: Resultsmentioning
confidence: 99%
“…They reported a significant change in orientation of focal mechanisms (maximum compressive stress 74° 13°relative to fault strike, compared to 62° 11°northwest and 49° 7°southeast) and suggested that this may result from stronger material within the gap. More recently, Bailey et al (2010) suggested that stress heterogeneity may be controlled by the complex-fault structures. They observed two clusters of earthquakes with primarily thrust mechanisms to the northwest and strike-slip mechanisms to the southeast of the Anza gap (Bailey et al, 2010).…”
Section: San Jacinto Fault Backgroundmentioning
confidence: 99%
“…More recently, Bailey et al (2010) suggested that stress heterogeneity may be controlled by the complex-fault structures. They observed two clusters of earthquakes with primarily thrust mechanisms to the northwest and strike-slip mechanisms to the southeast of the Anza gap (Bailey et al, 2010).…”
Section: San Jacinto Fault Backgroundmentioning
confidence: 99%
“…Heterogeneous distribution of stress has been inferred within fault zones from focal mechanisms by Bailey et al . [].…”
Section: Introductionmentioning
confidence: 99%